A Switchable and Compressible Carbon Nanotube Sponge Electrocapillary Imbiber. (13th October 2015) - Xue, Yahui; Yang, Yanbing; Sun, Hui; Li, Xiying; Wu, Shiting; Cao, Anyuan; Duan, Huiling
Abstract : Carbon nanotube sponges are lightweight, conductive, highly porous, and flexible. An integration of these properties is suitable for constructing high‐performance electrocapillary imbibers. Water imbibition into the sponges can be initiated at low potentials with tunable uptake rates and switched on and off reversibly. These controllable nanoporous imbibers have potential applications in a wide range of flexible micro‐ and nanofluidic systems.